THE ANTIPSYCHOTIC POTENTIAL OF MUSCARINIC ALLOSTERIC MODULATION - Bridges, Thomas M. (Drug News Perspect, 2010)
The cholinergic hypothesis of schizophrenia emerged over 50 years ago based on clinical observations with both anticholinergics and pan-muscarinic agonists. Not until the 1990s did the cholinergic hypothesis of schizophrenia receive renewed enthusiasm based on clinical data with xanomeline, a muscarinic acetylcholine receptor M(1)/M(4)-preferring orthosteric agonist. In a clinical trial with Alzheimer’s patients, xanomeline not only improved cognitive performance, but also reduced psychotic behaviors. This encouraging data spurred a second clinical trial in schizophrenic patients, wherein xanomeline significantly improved the positive, negative and cognitive symptom clusters. However, the question remained: Was the antipsychotic efficacy due to activation of M(1), M(4) or both M(1)/M(4)? Classical orthosteric ligands lacked the muscarinic receptor subtype selectivity required to address this key question. More recently, functional assays have allowed for the discovery of ligands that bind at allosteric sites, binding sites distinct from the orthosteric (acetylcholine) site, which are structurally less conserved and thereby afford high levels of receptor subtype selectivity. Recently, allosteric ligands, with unprecedented selectivity for either M(1) or M(4), have been discovered and have demonstrated comparable efficacy to xanomeline in preclinical antipsychotic and cognition models. These data suggest that selective allosteric activation of either M(1) or M(4) has antipsychotic potential through distinct, yet complimentary mechanisms.